Oxygen plasma treatment for reducing hydrophobicity of a sealed polydimethylsiloxane microchannel - Tan, Say-Hwa (2012)
Rapid prototyping of polydimethylsiloxane (PDMS) is often used to build microfluidic devices. However, the inherent hydrophobic nature of the material limits the use of PDMS in many applications. While different methods have been developed to transform the hydrophobic PDMS surface to a hydrophilic surface, the actual implementation proved to be time consuming due to differences in equipment and the need for characterization. This paper reports a simple and easy protocol combining a second extended oxygen plasma treatments and proper storage to produce usable hydrophilic PDMS devices. The results show that at a plasma power of 70 W, an extended treatment of over 5 min would allow the PDMS surface to remain hydrophilic for more than 6 h. Storing the treated PDMS devices in de-ionized water would allow them to maintain their hydrophilicity for weeks. Atomic force microscopy analysis shows that a longer oxygen plasma time produces a smoother surface.